CORRUPTION IN INDONESIA (Factor Analysis and Efforts That Need To Be Done) - La Ode Fiki (Universitas 17 Agustus 1945 Semarang, 2021)
Corruption is a crime that is categorized as an extraordinary crime because the impact of this crime will have an overall effect on people’s lives in a country. The corruption crime needs to be handled seriously by optimizing the penal system, increasing the punishment for the perpetrators of corruption. This article will discuss what factors lead to the emergence of criminal acts of corruption, secondly, how the efforts need to be made by law enforcement officers to overcome these problems. The study results show that criminal acts of corruption arise and are widespread due to several factors such as legal, political, economic factors, and so on, for this matter. It is necessary to take action from law enforcement in overcoming the problem by coordinating and punishing the perpetrators of corruption with the maximum punishment.